THE IMMUNOLOGICAL RESPONSE OF SWINE TO AFRICAN SWINE FEVER DNA VACCINE INDUCTION - Wardhani, Kadek Thalia Suryaningtyas Oka; Mahardika, I Gusti Ngurah Kade; Berata, I Ketut (Buletin Veteriner Udayana, 2025)
African Swine Fever (ASF) is a disease that attack swine with high mortality. DNA vaccine against ASF had been tested in mouse, but the research in swine has not been done. The purpose of this study is to evaluate swine immune response against ASF DNA vaccine and time effect of serum collection against antibodies of ASF virus. The method that had been used is vaccinating the swine with ASF DNA vaccine intramuscularly and measuring humoral immune response with ELISA on collected swine serum in weeks 0, 2, and 4. The result pointing that ASF DNA vaccine can induce production of antibodies in treatment group compared with control group with Optical Density (OD) increasing value in weeks 2 and 4. The serum time collection also do affect antibodies level in every weeks that had been observed, that is weeks 0, 2, and 4 with significant increase between week 0 and 2, but between week 2 and 4 the antibodies level is not affected significantly. This study is recommending further research to observe protection effect of ASF DNA vaccine by extending research duration and observation of celluler immune response to support vaccine effectiveness in field.